Effects of chlorogenic acid on growth, metabolism, antioxidation, immunity, and intestinal flora of crucian carp (Carassius auratus) - Jin, Xuexia; Su, Mengyuan; Liang, Yunxiang; Li, Yingjun (Frontiers in Microbiology, 2023)
In recent years, with the harm caused by the abuse of antibiotics and the increasing demand for green and healthy food, people gradually began to look for antibiotic alternatives for aquaculture. As a Chinese herbal medicine, leaf extract chlorogenic acid (CGA) of Eucommia ulmoides Oliver can improve animal immunity and antioxidant capacity and can improve animal production performance. In this study, Crucian carp (Carassius auratus) was fed with complete feed containing 200 mg/kg CGA for 60 days, to evaluate the antioxidant, immuno-enhancement, and regulation of intestinal microbial activities of CGA. In comparison to control, the growth performance indexes of CGA added fish were significantly increased, including final body weight, weight gain rate and specific growth rate (P<0.01), while the feed conversion rate was significantly decreased (P<0.01). Intestinal digestive enzyme activity significantly increased (P<0.01); the contents of triglyceride in liver (P<0.01) and muscle (P>0.05) decreased, and the expression of lipid metabolism-related genes in liver was promoted. Additionally, the non-specific immune enzyme activities of intestinal and liver tissues were increased, but the expression level of adenylate activated protein kinase gene involved in energy metabolism was not affected. The antioxidant capacity of intestinal, muscle and liver tissues were improved. Otherwise, CGA enhanced the relative abundance of intestinal microbe Fusobacteria and Firmicutes and degraded the relative abundance of Proteobacteria. In general, our data showed that supplementation with CGA in dietary had a positive effect on Carassius auratus growth, immunity and balance of the bacteria in intestine. Our findings suggest that it is of great significance to develop and use CGA as a natural non-toxic compound in green and eco-friendly feed additives.